Study on the Influence of Modified Multi-Walled Carbon Nanotubes to the Shear Strength of Urea-Formaldehyde Resin Adhesive - Huang, Jintian; Tie, Kunling; Pan, Yanfei (Asian Journal of Chemistry, 2013)
Multi-walled carbon nanotubes (MWCNTs) were modified successfully with concentrated sulfuric acid/nitric acid 3:1 (v/v) and anionic surfactant, then MWCNTs/urea-formaldehyde resin (UF) composites were prepared through mechanical mixing and ultrasonic method. The results show that the surface of MWCNTs was introduced carboxyl groups and the hydrophilic groups of -OSO32- after modification. Shear strength of MWCNTs/UF conposites increased by 90.7 % comparing with pure UF. The optimal proportion of sodium dodecyl sulfate (SDS)/MWCNTs is 2:1 (wt. ratio), which the modified MWCNTs could be dispersive in UF resin, the mixing time decreased by adding surfactant.